2021
DOI: 10.3390/agronomy12010098
|View full text |Cite
|
Sign up to set email alerts
|

European Grapevine Moth and Vitis vinifera L. Phenology in the Douro Region: (A)synchrony and Climate Scenarios

Abstract: The European grapevine moth (Lobesia botrana; Denis and Schiffermüller, 1775) is considered a key pest for grapevine (Vitis vinifera L.) in the Douro Region, Portugal. The phenology of both the grapevine and the pest has changed in the last decades due to the increase in temperature. Here, we assess the potential impact of climate change on the (a)synchrony of both species. The results show that the phenological stages (budburst, flowering and veraison) undergo an advancement throughout the region (at an ~1 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Other studies find similar results with asynchrony, especially between G3 and the veraison at the end of the century (Reis et al, 2021b).…”
Section: Towards a Mismatch Of Trophic Levels In Southern Europesupporting
confidence: 69%
“…Other studies find similar results with asynchrony, especially between G3 and the veraison at the end of the century (Reis et al, 2021b).…”
Section: Towards a Mismatch Of Trophic Levels In Southern Europesupporting
confidence: 69%
“…Besides, several factors must be considered when estimating these metrics. For instance, Reis et al [18] evaluated the impact of climate change on the phenology of both the grapevine in the Douro region to provide useful information to support strategies of management for the regional winegrowers and decision-makers, concluding that there are different dynamics in the phenology depending on elevation and thermal accumulation to reach a certain stage. The results indicating that this dynamic means that there are different timings of the phenology in the region.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted in recent years, using different models combined with climate change scenarios, to assess future changes in grapevine phenological timings (Webb et al ., 2007; Caffarra and Eccel, 2011; Xu et al ., 2012; Cuccia et al ., 2014; Fraga et al ., 2016a; 2016b; Ramos, 2017; Blanco‐Ward et al ., 2019; Costa et al ., 2019; Ramos and Martínez de Toda, 2020; Reis et al ., 2021). All of these studies showed that the main phenological stages (budbreak, flowering, veraison) and harvest would advance in the future, but with a more pronounced advancement foreseen for veraison and harvest than for the earlier stages.…”
Section: Introductionmentioning
confidence: 99%